Process Of Execution Of Liability Rights To Object Guaranteed To Debtors With A Promise Disabled - Djunaid Randiyo Muslimin (Sultan Agung Notary Law Review, 2020)
This study aims to: to find out how the force of law is the process of executing mortgage rights to objects guaranteed to debtors with defects in promise. The approach method in this research is empirical juridical law, the data source is obtained from the literature and the legal materials used are primary, secondary and tertiary legal materials which are then analyzed by means of qualitative analysis. Based on the results of this study it can be concluded that the execution of the object of guarantee of mortgage rights against debtors in default that this is motivated by article 6 of Act No. 4 of 1996 on Mortgage which states that "If the debtor fails to promise, the first Mortgage holder has the right to sell. the object of the Guarantee Rights on his own power through a public auction and taking the payment of the receivables from the proceeds of the sale. The purpose of this article is if the debtor is proven to be in default, then the creditor who holds the Mortgage has the right to carry out the execution of the collateral object through a public auction with the presence or absence of the promise to sell as stated in the APHT. If in APHT there is no promise or the collateral object has a problem then the execution against the object of permanent guarantee through a District Court Decision. This is based on SE-23 / PN / 2000 regarding instructions for auction implementation of mortgage rights, especially point 3 which states that "auction implementation without going through a court order cannot be carried out if the APHT does not contain the word promise as referred to in article 6 Jo article 11 paragraph 2 letter (e) UUHT or there are obstacles / lawsuit from the Debtor / third party, if this happens. The auction according to article 6 of the UUHT, namely that the auction should be able to be carried out on all collateral objects that are burdened with mortgage rights without seeing the presence or absence of promises and even though there are still obstacles in the form of claims from the debtor / other party against the object of guarantee. This is intended so that the creditor will no longer experience difficulties in executing the object of the guarantee of the mortgage, because of the difficulties that have caused creditors to continue to experience losses. Meanwhile, on the other hand, the revision of the regulations regarding the execution of mortgage rights is expected to create synchronization in the regulation itself and can provide legal certainty for creditors in executing the object of guarantee of mortgage rights without having to go through court because the process in court takes a long time and is expensive.